2002
DOI: 10.1016/s0960-9822(02)01388-x
|View full text |Cite
|
Sign up to set email alerts
|

Control of Lte1 Localization by Cell Polarity Determinants and Cdc14

Abstract: Restriction of Lte1 to the bud cortex depends on the cortical proteins Cdc42 and Kel1 and the septin ring. Cla4 and Cdc14 promote and demote Lte1 localization at and from the bud cortex, respectively, suggesting not only that the phosphorylation status of Lte1 controls its localization but also indicating that Cla4 and Cdc14 are key regulators of the spatial asymmetry of Lte1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
120
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(131 citation statements)
references
References 40 publications
11
120
0
Order By: Relevance
“…This phenotype is thought to occur in part because septin assembly at the incipient bud site is defective (28), which activates a morphogenesis checkpoint that inhibits cyclin-cdk (Clb-Cdc28) complexes required to drive G 2 /M progression (57). A second phenotype of cla4⌬ cells is a delay in mitotic exit (11)(12)(13). Mitotic exit is impaired because recent studies have indicated that Cla4 is required for phosphorylation of Lte1 (11,12), a guanine-nucleotide exchange factor for the Tem1 GTPase in the MEN (58).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This phenotype is thought to occur in part because septin assembly at the incipient bud site is defective (28), which activates a morphogenesis checkpoint that inhibits cyclin-cdk (Clb-Cdc28) complexes required to drive G 2 /M progression (57). A second phenotype of cla4⌬ cells is a delay in mitotic exit (11)(12)(13). Mitotic exit is impaired because recent studies have indicated that Cla4 is required for phosphorylation of Lte1 (11,12), a guanine-nucleotide exchange factor for the Tem1 GTPase in the MEN (58).…”
Section: Resultsmentioning
confidence: 99%
“…A second phenotype of cla4⌬ cells is a delay in mitotic exit (11)(12)(13). Mitotic exit is impaired because recent studies have indicated that Cla4 is required for phosphorylation of Lte1 (11,12), a guanine-nucleotide exchange factor for the Tem1 GTPase in the MEN (58). Cla4 is also required for Lte1 function as assessed by restricted localization of this exchange factor to the cortex of the bud (11).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Probably the best characterized function of Cla4 is the assembly of the septin ring, which plays a fundamental role in cytokinesis and cell compartmentalization (Weiss et al, 2000;Schmidt et al, 2003;Kadota et al, 2004;Versele and Thorner, 2004). In addition, Cla4 regulates mitotic entry and exit (Hö fken and Schiebel, 2002;Seshan et al, 2002;Sakchaisri et al, 2004). Very little is known about Skm1, and no clear function has been attributed to this PAK (Martín et al, 1997).…”
Section: Introductionmentioning
confidence: 99%